The Effect of Indole Acetic Acid on Forage Soybean under Drought Stress - Gizem Aksu (Turkish Journal of Agriculture: Food Science and Technology)
Drought is an important environmental stress that limits crop production in the world. Its importance has increased with global warming and it has become one of the most important factors limiting plant production. Soybean is the more source of obtaining and cheaper protein per unit area. Soybean has a widespread use in livestock because it contains valuable amino acids as well as high protein quality. The aim of this research is to diminish negative effect of drought stress in the forage soybean with indole acetic acid application. The experiment was carried out in the growth chamber according to a randomized block design with 4 doses (0-5-10-20 μM IAA) of indole acetic acid, 2 drought levels (0 and -0.5 MPa PEG-6000) and 3 replicate. Leaf length and width, leaf proportional water content, cell membrane damage and malondialdehyde (MDA) content of the plants were determined. The data were evaluated by analysis of variance using a statistical package program. According to the analysis of variance, all parameters were found to be statistically significant in drought x indole acetic acid interaction. Indole acetic acid applied to the forage soybean plant alleviated the damage caused by drought. For this reason, it is thought that it may be important to ensure less damage to plants grown under stress.